Evaluating the Effects of Increasing Sodium Diformate on Nursery Pig Growth Performance and Fecal Dry Matter - Katelyn N. Gaffield; Gracie J. Becker; Jessica L. Smallfield; Joel M. DeRouchey; Mike D. Tokach; Jason C. Woodworth; Robert D. Goodband; Troy Lohrmann; Christian Lückstädt; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2024)
A total of 360 weanling barrows (DNA 200 × 400, DNA; initially 13.1 ± 0.12 lb) were used in a 38-d growth trial to evaluate the effects of dietary sodium diformate on nursery pig growth performance and fecal dry matter. At weaning, pigs were randomly assigned to pens with five pigs per pen and 12 pens per treatment. There were six dietary treatments formulated to provided none, 0.40, 0.60, 0.80, 1.00, and 1.20% sodium diformate (Formi NDF, ADDCON, Nordic AS, Porsgrunn, Norway) added at the expense of corn. Experimental diets were fed in three phases: phase 1 from weaning to d 9, phase 2 from d 9 to 24, and phase 3 from d 24 to 38. From d 0 to 24 (phases 1 and 2), increasing sodium diformate improved (linear, P = 0.001) F/G. However, sodium diformate did not affect (P > 0.10) ADG or ADFI. From d 24 to 38 (phase 3) and overall (d 0 to 38), there was no evidence of differences (P > 0.10) in any of the growth performance criteria. There was no evidence for differences (P > 0.10) in fecal DM on d 9. However, fecal DM decreased (linear, P < 0.05) as sodium diformate increased on d 24 with pigs fed 0.40% sodium diformate having the highest percentage fecal DM. Additionally, there was evidence for a main effect of day (P < 0.001) with fecal DM being lower on d 24 compared to d 9. In conclusion, these data suggest increasing sodium diformate has the potential to improve feed efficiency in the early nursery period but did not affect performance in the late nursery.
Keywords: acidifier; growth performance; nursery pig; sodium diformate